FAKTOR-FAKTOR YANG MEMENGARUHI MANAJEMEN LABA PADA PERUSAHAAN SUBSEKTOR PROPERTI DAN REAL ESTATE - Gabriella, Bianca; Susanto, Salim (E-Jurnal Akuntansi TSM, 2025)
The influence of firm size, leverage, and cash flows from operating activities on earnings management practices was analyzed in property and real estate companies listed on the Indonesia Stock Exchange (IDX). The study utilized secondary data obtained from annual financial reports for the period 2021 to 2023. The sample was selected using purposive sampling based on specific criteria, resulting in 70 eligible companies. Data were analyzed using multiple linear regression. The results indicate that leverage and operating cash flows have a significant effect on earnings management, while firm size show no meaningful influence.